Implementation of Portland's Minimum Wage Ordinance: Need for a Community Based Organization Approach?. Issue 4 (7th December 2016) - Havlin, Michael
Abstract : There is a gap between what the city government of Portland Maine perceives and defines as successful minimum wage enforcement and what is actually occurring in workplaces. The city is taking an onerously complaint‐driven approach to enforcement that disregards the potential for a disconnect between violations occurring and violations being reported. Workplaces are fraught with institutional barriers like confusion, intimidation, and misinformation that prevent workers from knowing or exercising their rights. Outreach conducted collaboratively with the Southern Maine Workers Center has shown that these barriers have caused a number of violations of Portland's minimum wage ordinance that are going unreported.